In-vitro effect of a single application of CPP-ACP pastes and different fluoridated solutions on the prevention of dental caries around orthodontic brackets - Karla Lorene de França LEITE; Mariana Leonel MARTINS; Amanda Souza Nunes MONTEIRO; Thiago Isidro VIEIRA; Adílis Kalina ALEXANDRIA; Gustavo Miranda ROCHA; Andréa FONSECA-GONÇALVES; Matheus Melo PITHON; Yuri Wanderley CAVALCANTI; Lucianne Cople MAIA (Dental Press Editora, 2024)
ABSTRACT Objective: To assess the in-vitro effect of single applications of CPP-ACP pastes and different fluoridated solutions on the prevention of dental caries around orthodontic brackets. Material and Methods: Tooth/bracket sets (n=65) were immersed in artificial saliva (1h at 37ºC) and randomly subjected to single applications (100µL; 1min) of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP emulsion), CPP-ACP with fluoride (CPP-ACPF emulsion), solutions of titanium tetrafluoride (TiF4) or sodium fluoride (NaF), or no treatment (CG). Multispecies biofilm (5 x 105 CFU/mL) was formed in the presence of 2% sucrose. After 24 h, the pH and the concentration of total soluble fluoride (TSF) were analyzed by culture medium. The presence of active white spot lesions (WSL) evaluated by macroscopic examination and the percent surface mineral loss (%SML) were analyzed. Also, the topography of enamel was detected by analysis of scanning electron microscopy (SEM). The data was assessed by chi-square, Kruskal-Wallis, and Mann-Whitney tests (p < 0.05). Results: Fluoride-containing compounds led to a smaller pH reduction than did CPP-ACP and CG (p<0.05). There was difference in TSF between the groups (p<0.05), denoted as TiF4> NaF > CPP-ACPF > CPP-ACP > CG. Regarding the presence of WSL and %SML, the NaF group obtained lower values (p<0.05), while TiF4 and CPP-ACPF were similar (p>0.05). SEM demonstrated that fluoride-free groups had a larger surface dissolution. Conclusion: Fluoridated groups including solutions and CPP-ACPF were more effective than CPP-ACP in reducing enamel demineralization around orthodontic brackets after a single application.